Sistem Pendukung Keputusan Penilaian Kinerja Guru Menggunakan Metode Multi Attribute Utility Theory (MAUT) - Fikri, Muhammad Ihsanul; Haerani, Elin; Afrianty, Iis; Ramadhani, Siti (JURIKOM (Jurnal Riset Komputer), 2022)
State Junior High School 1 SIMPATI is a school located in Pasaman, West Sumatra. Schools are teaching institutions for students and are supervised by educators or teachers. The quality of education is very necessary for the progress of the school. For this reason, at the end of each semester at SMP N 1 Simpati an assessment is carried out for teacher perfor-mance, this assessment is to measure the quality and evaluate the performance of every teacher who teaches at the school. Analysis of teacher performance assessment using the Multi Attribute Utility Theory (MAUT) method. By applying the Multi Attribute Utility Theory (MAUT) method in the assessment process, the final result is ranked from the highest alternative value to the lowest alternative value. This Decision Support System is built on a Web-based basis with the PHP program-ming language and the Code Igniter framework. And the UAT test has been carried out on the system with 90% results, which means the application can be accepted for use, as well as blackbox testing where the application can run according to its function and is suitable for use in a teacher performance assessment decision support system